VALUES OF RELIGIOUS MODERATION IN THE PERSPECTIVE OF EDUCATIONAL PHILOSOPHY - Dinar Saharani; Henny Suharyati (International Journal of Teaching and Learning, 2024)
The role of education in shaping students' characters goes beyond the mastery of subject matter; it also involves the formation of moral and spiritual values. One crucial aspect in this regard is religious moderation, a concept that depicts a balanced and wise approach to the understanding and practice of religion. Thus, the purpose of this study is to examine the virtues of religious moderation from the standpoint of educational philosophy. The study includes a review of the literature and uses a descriptive qualitative methodology. According to the research's findings, tolerance, patriotism, resistance to radicalism and violence, and respect for local customs are among the virtues of religious moderation from the standpoint of philosophy of education. At-tawassuth, al-i'tidal, at-tasamuh, ash- shura, al-ishlah, al-qudwah, al-muwathanah, al-la'unf, and i'tiraf al-'urf are among the Islamic ideals of religious moderation.